V-LAMOT: A Cognitive-Load Optimized Virtual Lab for Three-Phase Motor Control - Isnaini, Muhammad; Purba, Sukarman; Dewy, Mega Silfia; Solihin, Muhammad Dani; Silitonga, Agnes Irene (Journal of Educational Technology and Learning Creativity, 2026)
Purpose of the study: This study aims to design and validate V-LAMOT, a web-based virtual laboratory for three-phase motor starting simulation. The system is intended to address limitations of physical laboratories by providing an accessible and safe environment while maintaining conceptual accuracy and supporting the development of practical motor control skills. Methodology: The study adopted the Systems Development Life Cycle (SDLC) to develop the V-LAMOT platform using HTML5, CSS, JavaScript, and state-machine modeling. The design was guided by Cognitive Load Theory principles. Data were obtained through expert validation instruments and the System Usability Scale (SUS), and analyzed using Shapiro–Wilk tests, one-sample t-tests, Cohen’s d, and Pearson correlation with 30 students. Main Findings: Expert validation indicated high feasibility, with conceptual accuracy reaching a mean score of 4.50/5. SUS evaluation produced an overall score of 78.83 (“Good”), with learnability scoring highest at 82.00. All usability measures were significantly above the benchmark (p < 0.001) with large effect sizes (d > 0.8). A strong correlation between usability and learnability (r = 0.823) suggested effective cognitive load reduction. Novelty/Originality of this study: This study presents an integrated virtual laboratory that combines state-machine modeling with Cognitive Load Theory-based interface design for three-phase motor control. Unlike conventional simulations, V-LAMOT integrates multiple motor starting methods in one environment and empirically links usability, learnability, and cognitive load reduction, advancing virtual laboratory development through systematic integration of technical accuracy and pedagogical principles.